Effects Of Individual Characteristics On Expatriates' Adjustment And Job Performance - Muhammad Awais Bhatti,; Sharan Kaur,; Mohamed Mohamed Battour (Emerald Group Publishing Limited, 2024)
Purpose Researchers have been focusing on the predictors of expatriates' adjustment and job performance at different levels (individual level, organizational level and societal level), but still some of the predictors have been ignored or unclear in the expatriate literature. The purpose of this paper is to develop a comprehensive framework in order to better understand the role of individual factors in expatriate adjustment and job performance.